Medicinal Plants Diversity Used by Balinese in Buleleng Regency, Bali - Putri Sri Andila; I Gede Tirta; Tri Warseno; Sutomo Sutomo (Universitas Gadjah Mada, 2023)
The Lontar Usada Bali is a collection of the science of traditional medicine recorded in the lontar leaves. It contains information about the diversity of medicinal plants and treatment procedures used by Balinese for generations. However, most of the information stored in the lontars is only known by the Balians (Traditional Healers). The aim of the study was to investigate and document the diversity of medicinal plants known by Balians in Buleleng Regency, Bali Province, Indonesia. Direct interview with Balians, combined with purposive sampling (for the usada plants), was used in this study and conducted in August-September 2022. The data obtained comprised plant species, habitat, habitus, local names, plant parts used, and how they were used. The data were analysed qualitatively and quantitatively using diagrams, graphs, and tables and measured by the use-value index. Sixty-five species and 37 families of plants were recorded as a medicinal plant. The most widely used plant families by Balians were Zingiberaceae, Poaceae, Rutaceae, Euphorbiaceae, Lamiaceae, Lauraceae, and Malvaceae. In most cases, leaves were used, followed by tubers, fruits, and other parts. Maceration and powder or mushy were the primary modes of making herbal medicine, and external application was the most common method of drug administration. Most medicinal plants were obtained from the home garden, taken from nature, or bought in the market. Several diseases often treated by Balians were convulsions, itching, cramps, headache, black magic, stroke, herpes and tumor/cancer. This research is important to complete the ethnobotanical data on the diversity of medicinal plants in Bali. This data is important information for the development of new drugs and must be maintained for sustainability.